The Relationship Between the Adverse Events and Efficacy of Sorafenib in Patients With Metastatic Renal Cell Carcinoma: A Multicenter Retrospective Study from Northwest China. Issue 49 (December 2015) - Zheng, Yu; Wang, Fuli; Wu, Guojun; Zhang, Longlong; Wang, Yangmin; Wang, Zhiping; Chen, Peng; Wang, Qing; Lu, Jingyi; Wang, Yujie; Li, Peijun; Wang, Jian; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The aim of the study is to evaluate the relationship between the adverse events and efficacy of sorafenib in patients with metastatic renal cell carcinoma (mRCC), with a purpose to guide the judgment of efficacy in sorafenib treatment. Eighty-three mRCC patients who received sorafenib therapy at northwest China were studied retrospectively. Univariate and multivariate analyses were performed to correlate tumor response, progression-free survival (PFS), and overall survival (OS) with adverse event types and grades. Among 83 patients who underwent sorafenib therapy, 2 cases (2.4%) had completed response (CR), 14 cases (16.9%) had partial response (PR), 57 cases (68.7%) had stable disease (SD), and 10 cases (12.0%) developed progressive disease (PD). The median PFS and OS were 15.0 and 29.0 months, respectively. The most frequent grade 1 or 2 adverse events included hand-foot syndrome (68.7%), diarrhea (54.2%), and alopecia (51.8%). The most common grade 3 or 4 adverse events were hand-foot syndrome (6.0%), hypertension (4.8%), and diarrhea (3.6%). The frequency and severity of adverse events correlated with tumor response rate (both with P < 0.05). Multivariate analysis showed the independent predictors of better PFS included rash (OR 0.307, 95%CI 0.148–0.636, P  = 0.001) and diarrhea (OR 0.391, 95%CI 0.169–0.783, P  = 0.008). Elevated transaminase was the independent predictor of poor PFS (OR 2.606, 95%CI 1.299–5.532, P  = 0.012). For OS, rash (OR 0.473, 95%CI 0.253–0.886, P  = 0.019) and diarrhea (OR 0.321, 95%CI 0.171–0.605, P  = 0.000) correlated with better OS. Sorafenib-related adverse events are associated with efficacy in patients with mRCC from northwest China. Rash and diarrhea are independent protective factors of both PFS and OS, and elevated transaminase is an independent risk factor of PFS. A large prospective study is warranted.